Ferrocenyl‐Functionalized Tetranuclear Gold(I) and Gold(I)–Copper(I) Complexes Based on Tridentate Phosphanes. Issue 28 (5th August 2013) - Dau, Thuy Minh; Shakirova, Julia R.; Doménech, Antonio; Jänis, Janne; Haukka, Matti; Grachova, Elena V.; Pakkanen, Tapani A.; Tunik, Sergey P.; Koshevoy, Igor O.
Abstract: Tetranuclear Au I –Fe II dimetallic and Au I –Cu I –Fe II trimetallic complexes bearing ferrocenyl (Fc) groups have been assembled by using two triphosphane ligands, namely, (PPh2 CH2 )2 PPh (dpmp) and (PPh2 )3 CH (tppm). The compositions and structural type of the clusters are dependent on the stereochemistry of the P donor ligands. The complexes [tppmAu3 Cu(C2 R)3 ]PF6 [R = Fc (1 ) and 4‐C6 H4 ‐Fc (2 )] adopt a trigonal pyramidal Au3 Cu arrangement of the coordinating metal core, whereas for the compounds with the linear triphosphane [Au4 (dpmp)2 (C2 R)2 ](PF6 )2 [R = Fc (3 ) and 4‐C6 H4 ‐Fc (4 )], a planar rhomboidal Au4 framework was found. Clusters1 –4 were characterized by NMR spectroscopy and ESI‐MS measurements. The solid‐state structures of1, 3, and4 have been determined by X‐ray crystallography. The electrochemical properties of1 –4 were studied and revealed redox processes attributed to the Fc functions. Oxidation of the Fc units in1, 2, and4 occurs independently. In3, an electron transfer process mediated by the Au4 metal core was observed. Abstract : Tetranuclear Au I and Au I –Cu I clusters decorated with ferrocenyl groups demonstrate redox behavior dependent on the composition of the metal core. The charge mobility is successfully mediated by the Au4 metal core.